Synthesis, characterization and antimicrobial activity of the Schiff bases derived from 2,4-disubstituted thiazoles and 3-methoxysalicylaldehyde, and their cobalt(II), copper(II), nickel(II) and zinc(II) complexes - Yilmaz, I; Çukurovali, A (Kluwer Academic Publ, 2003)
Two new Schiff base ligands containing 2,4-disubstituted thiazoles and cyclobutane rings, 4-(1-methyl-1-phenylcyclobutane-3-yl)-2-(2-hydroxy-3-methoxybenzylidenehydrazino)thiazole ((LH)-H-1), 4-(1-methyl-1-p-xylylcyclobutane-3-yl)-2-(2-hydroxy-3-methoxybenzylidenehydrazino) thiazole ((LH)-H-2) and their mononuclear complexes with a 1: 2 metal-ligand ratio have been prepared from acetate salts of Co-II, Cu-II, Ni-II and Zn-II in EtOH. The authenticity of the ligands and their complexes have been established by microanalyses, i.r., C-13- and H-1-n.m.r. spectra, and by magnetic susceptibility and conductivity measurements. The complexes are mononuclear. Thermal properties of the ligands and complexes have been studied by t.g.a. and d.s.c. techniques. Antimicrobial activities of the ligands and their complexes have been tested against six different microorganisms; three are yeast and three are bacteria. One of the ligands and many of the complexes were found to be active against some of the microorganisms studied.
Keywords: Metal-Complexes; Ligands